1821 Me. Laws 98-99 - (:unkn) unknown (My University, 1821)
Ch. 25, § 5: An Act for the Prevention of Damage by Fire, and the Safe Keeping of Gun Powder: Authorized local "selectmen" to search for gun powder, which they may have reason to suppose to be concealed or kept, contrary to the rules and regulations which shall be established in such town, according to the provisions of this Act, first having obtained a search warrant therefor according to law.
Keywords: GUNPOWDER - STORAGE